FOOD IS AN EMOTION: A READING ON HOW FOOD INFLUENCE OUR MIND IN THE NOVEL ‘LIKE WATER FOR CHOCOLATE’ BY LAURA ESQUIVEL - GAYATHRY S; CHELLERIAN, B. SONIA (International Journal of Psychosocial Rehabilitation, 2020)
Food had been an integral part of human life. For decades we human beings are insane for food and we lives for food. For some food means to explore the taste and for some is to explore the culture and the deep connection between food and our emotions. The varieties of taste and ingredients make each food unique from each other. From the biblical era of Adam and Eve food, i.e., apple which became a symbol of sin has been an essential role in the world. So, food plays both positive and negative roles in the lives of humans. In the novel ‘Like Water for Chocolate’ by Laura Esquivel the twelve recipe instalment play a vital role in expressing the protagonist’s emotion, for instance emotions like anger, suffocation, love and pain. Thus the novel becomes a remarkable narration of emotion overflowing through food.